Assessment of quality and safety at critical control points of cow's milk produced in Northern Mindanao - Hebron, I. U.; Cuizon, T. S.; Furog, A. C.; Gonzaga, J. M.; Maglacion, L. N. A.; Hallasgo, M. H. C.; Taculod, T. A. (International Journal of Agricultural Technology, 2025)
Results showed that 60% of raw milk samples tested positive in Alcohol Precipitation Test, but confirmatory tests with Clot on Boiling proved the samples otherwise. Methylene Blue Reduction Test at the different critical control points rated very good implying their acceptability for processing. Physico-chemical tests indicated butterfat at 4.58%, Solid Non-Fat at 8.92%, protein at 3.52%, Lactose at 4.72%, and Brix at 9.2%. Organoleptic quality tests showed acceptable appearance, color, and sedimentation. However, microbial culture shows E. coli and Total Coliform Counts are present beyond the acceptable limits in processed flavored milk, but none in plain pasteurized milk. The fat, SNF, and lactose contents were beyond minimum standards, while the protein was a little below the acceptable limits. These results may be attributed to the farms’ compliance with the Risk Management Plan for milking required by the National Dairy Authority that ensured the production of safe and quality milk. Regular monitoring and evaluation with further tests for farm hygiene and sanitation with bacterial tests may be done in the future.